The Development of a Human Respiratory Mucosa-on-a-Chip Using Human Turbinate-Derived Mesenchymal Stem Cells - Do Hyun Kim; Sang Hi Park; Mi-Yeon Kwon; Chae-Yoon Lim; Sun Hwa Park; David W. Jang; Se Hwan Hwang; Sung Won Kim (Medicina)
Background and Objectives: This study aimed to investigate the influence of a respiratory mucosa-on-a-chip on the respiratory epithelial differentiation potential of human nasal inferior turbinate-derived stem cells (hNTSCs). Materials and Methods: After isolating hNTSCs from five patients, we divided the samples from the patients into the study group with a mucosa-on-a-chip and the control group with conventional differentiation (using conventional differentiation methods). The respiratory epithelial differentiation potential of hNTSCs was analyzed by histology and gene expression. Results: In the quantitative analysis, PCR showed that the hNTSCs expressed the cytokeratin genes (KRT13, 14), transformation-related protein P63 (TP63), and vimentin of basal cells in the airway epithelium at higher levels, but cytokeratin genes (KRT6) at lower levels, in the mucosa-on-a-chip than in conventional differentiation. In the cytokine analysis (GM-CSF, IFNr, IL-1a, IL-1b, IL-4, IL-5, IL-10, IL-12(p70), IL-13, IL-17A, IL-17E/IL-25, RANTES, TNFa, IL-6, and IL-8), the expressions of IFNr, IL-13, RANTES, TNFa, IL-6, and IL-8 were significantly upregulated in the mucosa-on-a-chip than in conventional differentiation. Conclusions: We conclude that the human respiratory mucosa-on-a-chip using human turbinate-derived mesenchymal stem cells allows the respiratory differentiation of hNTSCs and shows the difference in gene and cytokine expression, which could serve as an alternative to conventional differentiation for the production of functionally competent hNTSCs for future clinical applications.